Participation of informal institutions in ecotourism management at Clungup Beach in Southern Malang - Harsuko Riniwati; Nuddin Harahab; Zaenal Abidin (Proceedings of AICS - Social Sciences, 2017)
Research question on how informal institutions should participate in ecotourism development motivated the researchers to conduct this study. This research was aimed to analyze the informal institutions participation in ecotourism management at Clungup Beach, Southern Malang Regency. Has the participation of informal institutions been maximum? How informal institutions should increase their participation in achieving ecotourism goals at Clungup beach? The data were obtained from structured questionnaires which were distributed to all ecotourism managers at Clungup beach. The research variables consisted of four dimensions: attendance frequency in meeting, group participation in discussion, involvement in physical activity and willingness to contribute or donate. Then, the data were analyzed by using MDS (Multidimensional Scaling). The results showed that the participation of informal institutions in ecotourism management at Clungup beach has not been optimal. Thus improvements to all dimensions are needed: attendance at meetings, group participation in discussions, involvement in physical activities and willingness to contribute or donate. Suggestions based on this research are increasing the participation of informal institutions in ecotourism management by giving equal responsibility, freedom in decision making, authority in proposing idea and compulsion with positive aims such as imposing ideas and demanding them to participate in discussions and other activities.